2010
DOI: 10.1590/s1517-83822010000300010
|View full text |Cite
|
Sign up to set email alerts
|

Distribution, detection of enterotoxigenic strains and antimicrobial drug susceptibility patterns of Bacteroides fragilis group in diarrheic and non-diarrheic feces from Brazilian infants

Abstract: Despite the importance of gastrointestinal diseases and their global distribution, affecting millions of individuals around the world, the role and antimicrobial susceptibility patterns of anaerobic bacteria such as those in the Bacteroides fragilis group (BFG) are still unclear in young children. This study investigated the occurrence and distribution of species in the BFG and enterotoxigenic strains in the fecal microbiota of children and their antimicrobial susceptibility patterns. Diarrheic (n=110) and non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
(27 reference statements)
0
6
1
Order By: Relevance
“…29 Several studies have reported similar prevalence of B. fragilis, B. vulgatus, and P. distasonis in human fecal microbiota. 30,31 In this study, B. vulgatus was found in high prevalence in the nontreated children than the treated ones (70% vs. 19.3%, respectively), whereas P. distasonis was observed more in the antibiotic-treated children (in 20% control children vs. 38.7% antibiotic-treated). This suggested that the species B. fragilis and B. vulgatus are sensitive and P. distasonis is resistant toward antibiotic therapy.…”
Section: Discussionmentioning
confidence: 49%
“…29 Several studies have reported similar prevalence of B. fragilis, B. vulgatus, and P. distasonis in human fecal microbiota. 30,31 In this study, B. vulgatus was found in high prevalence in the nontreated children than the treated ones (70% vs. 19.3%, respectively), whereas P. distasonis was observed more in the antibiotic-treated children (in 20% control children vs. 38.7% antibiotic-treated). This suggested that the species B. fragilis and B. vulgatus are sensitive and P. distasonis is resistant toward antibiotic therapy.…”
Section: Discussionmentioning
confidence: 49%
“…A very good activity of meropenem has been reported by Oteo et al (2000) With 100% of susceptibility, but a higher rate of resistance was reported by Ferreira et al (2010) (18.2%).…”
Section: Discussionmentioning
confidence: 88%
“…In a study performed by Ferreira et al (2010) in Brazil, the authors reported entirely different results, where P. distasonis was the major species (19.1%), followed by B. fragilis (17.0%), B. vulgatus (17.0%), B. caccae (2.1%) and P. merdae (2.1%).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To this end, 20% of the DNA samples obtained from different cities were used. Primers were designed to amplify a 1,067 bp sequence of the 16S rDNA gene of bacteria (Ferreira et al 2010). For amplification, 5 μL of the extracted material was used.…”
Section: Kato-katz Technique -mentioning
confidence: 99%